Credit Controls and Banking Obligations - Ashwaq Abdo Hazzazi (International Journal of Law Research and Studies, 2025)
This study aims to clarify the nature of bank credit and the controls for granting it to customers according to the position of the Saudi regulator and compare it with the Jordanian legislator. The study also addressed the obligations that banks must take into account when conducting credit business in order to reduce credit risks that lead to default. In addition, it is possible that violating these duties will result in civil or criminal liability. The study relied on the comparative analytical approach through analyzing and discussing the Saudi texts and regulations related to the subject of the study. The comparative approach was used by stating the position of the Jordanian legislator, and the study reached a number of results, the most important of which are: that bank credit is one of the important means of employing funds, whether through participation and support for investment projects or through providing loans and financial amounts to customers. Also, the banks’ commitment to credit study is considered a positive procedure that includes collecting information from different sources in order to have a clear and comprehensive picture of the customer seeking credit, in addition to the fact that the banks’ commitment to information, advice and consultation achieves complete protection for the customer and the bank at the same time. The study also reached a number of recommendations, the most important of which are: We recommend that the Saudi regulator explicitly stipulate a comprehensive and precise definition of bank credit, similar to the Jordanian legislator. We also recommend that Saudi banks pay attention to their human cadres working under the credit operations department, by qualifying and training them scientifically and legally, in order to keep pace with all developments occurring in the banking sector on an ongoing basis.
Keywords: Bank Credit; Bnks; Customer; Obligations